Political Law Protection and Management Environment Towards Indonesian Ecocracy - Wida Azlina; Ismaidar Ismaidar; Tamaulina Br. Sembiring (Green Social: International Journal of Law and Civil Affairs, 2025)
This article explores protection and environmental political laws in regard to economic management in Indonesia. there are two main problems that should be analyzed, (1) how is the protection and environmental political laws in Indonesia? And (2) how is the protection and environmental political laws in Indonesia in reaching Indonesia's economy. This is normative legal research by statutory and conceptual approach. It is then analyzed through law theory and law political concept as the basis for discussing the matters. The discussion is exploring protection and environmental political laws in Indonesia nowadays heading to democratic and responsive. Legal politics that is democratic and responsive provides a way to achieve the goals of Indonesia's economy.